Harmonizing the mind: - Liudmyla Vasylevska-Skupa; Liudmyla Onofriichyk; Olena Teplova; Kateryna Kushnir; Iryna Shvets (Convergências - Revista de Investigação e Ensino das Artes)
This study delves into the psychological effects of vocal therapy on university music students, addressing a gap in research on targeted mental health interventions for this group. Amidst the unique pressures of music education, this research examines how vocal therapy influences students' coping strategies, social connectedness, mental health, and resilience. Utilizing various validated instruments like the Kenny Music Performance Anxiety Inventory (K-MPAI), Short Form-36 (SF-36), UCLA Loneliness Scale, Coping Inventory for Stressful Situations (CISS), and the Connor-Davidson Resilience Scale (CD-RISC), the study compares students undergoing vocal therapy with those who are not. Results indicate a significant reduction in performance anxiety, improved general health and mental well-being, decreased feelings of loneliness, enhanced coping strategies, and increased resilience in students participating in vocal therapy. These findings underscore the efficacy of vocal therapy as a comprehensive intervention, advocating for its integration into university mental health services. This study contributes to the growing field of music therapy and mental health, offering essential insights for educational institutions, mental health professionals, and music educators.